SKOPIA (Serikat Pendidikan Komplementer Ibu dan Anak) sebagai Strategi Pencegahan Stunting Dengan Terapi Komplementer Berbasis Aplikasi - Selasih Putri Hadi; Riska Ismawati Hakim (Malahayati Nursing Journal, 2023)
ABSTRACT Health problems that arise in developing countries, including Indonesia, one of which is micronutrient deficiencies, especially in children under the age of 5 years, including stunting nutrition problems. This can be done in a practical, easy and safe stunting prevention effort to be taught to the community by doing complementary activities. This posyandu activity cannot be separated from the role of cadres. The role of cadres is very important as a driver and determinant of success in monitoring children's growth and development. For this reason, the government has launched an electronic application program to support the promotion process and public health services. To develop the SKOPIA application (Union of Complementary Mother and Child Education) as a Stunting Prevention Strategy with Complementary Therapy. This study uses the RD method with the development of ADDIE. The study was conducted in the Grabag 2 Work Area with the respondents being mothers of under-five Posyandu cadres with 19 respondents, the sample selection was using purposive sampling method. The inclusion criteria for cadres are 20-35 years old, physically and mentally healthy, willing to be a participant, have a mobile phone. The research instrument is a closed questionnaire to see the feasibility of the material, media and user aspects. The questionnaire has been tested through previous validity judgment. The results of the application feasibility assessment from the material aspect an average score of 67.67 with a very feasible category, the application feasibility from the media aspect an average score of 73.33 with a decent category, the feasibility of the application from a small group as much as 130.1 with a category very feasible, and the feasibility of the application from users as many as 125,21 with a very decent category. The Skopia application can be recommended as a medium of information and education for posyandu cadres, especially child health in alleviating stunting in children. Keywords: Application, Toddler, Complementary, Stunting  ABSTRAK Masalah kesehatan yang muncul di negara berkembang termasuk di negara Indonesia salah satunya adalah kekurangan mikronutrien, khususnya pada anak dibawah usia 5 tahun, diantaranya masalah gizi stunting. Hal ini dapat dilakukan usaha pencegahan stunting yang praktis, mudah dan aman untuk diajarkan ke masyarakat dengan melakukan komplementer. Kegiatan posyandu ini tidak lepas dari peran kader. Peran kader sangat penting sebagai penggerak dan penentu keberhasilan dalam pemantauan tumbuh kembang anak. Untuk itu pemerintah mencanangkan adanya program elektronik aplikasi untuk mendukung proses promosi dan pelayanan kesehatan masyarakat. Mengembangkan aplikasi SKOPIA (Serikat Pendidikan Komplementer Ibu dan Anak) sebagai Strategi Pencegahan Stunting Dengan Terapi komplementer. Penelitian ini menggunakan metode RD dengan pengembangan ADDIE. Penelitian dilakukan di Wilayah Kerja Grabag 2 dengan respoden ibu kader posyandu balita dengan jumlah responden 19 orang, pemilihan sample dengan metode purposive sampling. Kriteria inklusi usia kader 20-35 tahun, sehat jasmani rohani, bersedia menjadi partisipan, memiliki handphone. Instrumen penelitian berupa kuesioner tertutup untuk melihat kelayakan dari aspek materi, media dan user. Kuesioner telah diuji melalui validity judgment sebelumnya. Hasil penilaian kelayakan aplikasi dari aspek materi rata-rata skor sebanyak 67,67 dengan kategori sangat layak, kelayakan aplikasi dari aspek media rata-rata skor sebanyak 73,33 dengan kategori layak, kelayakan aplikasi dari kelompok kecil sebanyak 130,1 dengan kategori sangat layak, dan kelayakan aplikasi dari user sebanyak 125,21 dengan kategori sangat layak. Aplikasi SKOPIA dapat direkomendasikan sebagai media informasi dan pendidikan untuk para kader posyandu khususnya kesehatan anak dalam pengentasan stunting pada anak Kata Kunci: Aplikasi, Balita, Komplementer, Stunting